Pengaruh Diabetes Self Management Education (DSME) terhadap Resiko Terjadinya Ulkus Diabetik pada Pasien Rawat Jalan dengan Diabetes Mellitus (DM) Tipe 2 di RSD dr. Soebandi Jember (The Influence of Diabetes Self Management Education (DSME) to The Risk - Alvinda yuanita; Wantiyah Wantiyah; Tantut Susanto (Pustaka Kesehatan, 2014)
Type 2 Diabetes Mellitus (DM) is a glucose metabolism disorders caused by insulin resistance and impaired of insulin secretion and it can cause any chronic complications, such as diabetic ulcers. Diabetes Self Management Education (DSME) can facilitate patients’s knowledge, skills, and abilities for self-care to prevent diabetic ulcers. This research was intended to analyze the influence of DSME to the risk of diabetic ulcers on Type 2 DM outpatients. The research method was quasi experimental with pre-test and post-test with control group design and used consequtive sampling with 40 Type 2 DM respondents divided into 2 groups. Data were analyzed by using Paired T-test and Independent T-test with 95% of CI. The research results showed that P value of Paired T-test in experimental group is 0,000 and 0,015 in control group, while P value of Independent T-test was 0,001 (p < α ; α = 0,05). The conclusion of this research is there was an influence of DSME to reduce the risk of diabetic ulcers on Type 2 DM outpatients in dr. Soebandi Hospital Jember. It is suggested that nurses can provide DSME to prevent diabetic ulcers on Type 2 DM patients and using DSME as a health promotion program.   Keywords: diabetes mellitus, diabetic ulcers, DSME, self care